The Influence of Transformational Leadership, Motivation, and Discipline on Teacher Performance at Muhammadiyah Senior High School Martapura, Banjar Regency, South Kalimantan Province - Kadir, Abdul; Audah, Ali; Fatih, Hardika Muhammad; Badrian, Badrian; Jahra, Pati Matu (Universitas Hang Tuah, 2025)
This study aims to examine the influence of transformational leadership, motivation, and discipline on teacher performance at SMA Muhammadiyah Martapura, Banjar Regency, South Kalimantan Province. The research employed a quantitative approach using a survey method, with the entire population of 32 teachers selected as respondents through total sampling. Data were collected through literature review, questionnaires, interviews, and documentation, and analyzed using multiple linear regression. The results indicate that simultaneously, the three independent variables transformational leadership (X1), motivation (X2), and discipline (X3) have a significant effect on teacher performance (Y), with an F-value of 628.218 > F-table value of 3.63 and a significance level of 0.000 < 0.05. Partially, each variable also has a significant positive effect, as shown by t-values greater than the t-table and significance values below 0.05. Transformational leadership is found to be the dominant variable influencing teacher performance, with the highest regression coefficient of 0.895. The coefficient of determination (R²) is 0.993, indicating that 99.3% of the variance in teacher performance can be explained by the three independent variables.